A study of child-rearing practices in Tacloban City - Pelino, Hermanita L. (Leyte-Samar Studies, 1987)
The Philippines is a child-oriented society. The family is considered not complete without children because their companionship is sought not only by parents and older siblings but by relatives and neighbors as well. Also, children are eagerly desired since they are considered as assets to a family.